Consistent modified gravity: dark energy, acceleration and the absence of cosmic doomsday - Abdalla, MCB; Nojiri, S.; Odintsov, S. D. (Iop Publishing Ltd, 2005)
We discuss modified gravity which includes negative and positive powers of curvature and provides gravitational dark energy. It is shown that in GR plus a term containing a negative power of curvature, cosmic speed-up may be achieved while the effective phantom phase (with w less than -1) follows when such a term contains a fractional positive power of curvature. Minimal coupling with matter makes the situation more interesting: even 1/R theory coupled with the usual ideal fluid may describe the (effective phantom) dark energy. The account of the R(2) term (consistent modified gravity) may help to escape cosmic doomsday.